Measuring the Performance of IT Governance According to COBIT5 Framework by Using the Balanced Scorecard (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research aims to clarify the COBIT5 framework for IT governance and to develop of a criterion based on Balanced Scorecard that contributes in measuring the performance of IT governance. To achieve these goals, the researchers adopted the deductive approach in the design of balanced scorecard to measure the IT governance at the Bank of Baghdad that was chosen because it relied heavily on IT.The research has reached a number of conclusions, the most important of which is that the performance of IT department in the Bank of Baghdad falls within the good level that requires constant monitoring, the most committed items of Balanced Scorecard by the Bank were customer, internal operation, growth and finally the financial item; IT governance is a part of corporate governance which contributes in IT control and in achieving better risk management; the use of the COBIT5 framework represents a support of the whole corporate governance system; the use of Balanced Scorecard within COBIT5 framework contributes in evaluating the performance of the IT departments and ensuring the achievement of their strategic goals with possibility of identifying the weaknesses in their performance and the taking the necessary actions to manage and control them.